Desmoplastic Melanoma Arising after 1,064 nm q-Switched Nd:YAG Laser of a Suspected Solar Lentigo - Leah Cohen; Sonali Nanda; Martin Zaiac (Case Reports in Dermatological Medicine)
Objectives. To present a case of desmoplastic melanoma (DM) arising after laser therapy of a suspected solar lentigo with the 1,064 nm Q-switched (QS) Neodymium:Yttrium-Aluminum-Garnet (Nd:YAG) laser and discuss the safety of treating suspected solar lentigines with laser therapy. Methods. Case presentation with discussion. Results. We describe a patient who developed DM after 1,064 nm QS Nd:YAG laser therapy to a suspected solar lentigo. Conclusions. Limited generalizable studies regarding the safety of laser therapy for solar lentigines exist, specifically for the 1,064 nm QS Nd:YAG laser. Therefore, we recommend caution is taken when considering laser therapy for these lesions, as well as strong consideration for histologic confirmation prior to therapy.